2020
DOI: 10.3390/ijerph17062098
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Daily and Non-Daily Use of Heated Tobacco Products with Combustible Cigarettes: Findings from the 2018 ITC Japan Survey

Abstract: Use of heated tobacco products (HTPs) among current smokers is becoming increasingly popular in Japan. This study aims to compare characteristics and tobacco-related behaviors among concurrent users of HTPs and combustible cigarettes (n = 644) with exclusive smokers (n = 3194) or exclusive HTP users (n = 164). The secondary aim was to explore heterogeneity within concurrent use subgroups. Data were from Wave 1 of the ITC Japan Survey, a nationally representative web survey conducted from February to March 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 40 publications
4
24
1
1
Order By: Relevance
“…Compared with CC-only users, HTP users were more likely to perceive HTPs to be less harmful than CCs. Consistent with these results, a previous study found that HTP-only users and dual users of HTPs and CCs were more likely to believe that HTPs were less harmful to users than CCs, compared with CC-only users [ 16 ]. It is common for some tobacco product users to choose specific products which they perceive as less harmful because of their favorable perceptions towards these products [ 21 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Compared with CC-only users, HTP users were more likely to perceive HTPs to be less harmful than CCs. Consistent with these results, a previous study found that HTP-only users and dual users of HTPs and CCs were more likely to believe that HTPs were less harmful to users than CCs, compared with CC-only users [ 16 ]. It is common for some tobacco product users to choose specific products which they perceive as less harmful because of their favorable perceptions towards these products [ 21 , 22 , 23 , 24 ].…”
Section: Discussionsupporting
confidence: 74%
“…Even though one of the reasons for using HTPs was to stop smoking [ 6 , 12 ], several studies have shown no significant association between the use of HTPs and smoking cessation-related behaviors, including attempts or intentions to quit smoking [ 7 , 15 , 16 ]. Moreover, adolescent HTP users were less likely to become former CC smokers despite multiple attempts at smoking cessation [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study does not address the extent to which individual cigarette smokers are substituting HTPs for conventional cigarettes. A recent study suggests that most HTP users in Japan are also concurrently smoking cigarettes [13]. That said, these data do suggest that in Japan at least, the decline in cigarette sales has been accelerated by the introduction of HTPs.…”
Section: Discussionmentioning
confidence: 91%
“…There have been numerous studies that evaluate the association between e-cigarette use and intention to quit cigarette smoking, some of which included an in-depth analysis in relation to cigarette-smoking frequency (e.g., daily versus non-daily smoking) [ 16 , 17 ] or daily cigarette consumption (e.g., number of cigarettes smoked per day) [ 18 , 19 ]. Meanwhile, other studies focused on the association between HTP use and intention to quit cigarette smoking [ 20 , 21 , 22 ]. While previous studies of HTPs have considered the association with regard to cigarette-smoking frequency, they have not comprehensively evaluated the influence of cigarette-smoking intensity.…”
Section: Introductionmentioning
confidence: 99%